Proposal for the management of myopic traction maculopathy based on the new MTM staging system. Issue 6 (November 2021) - Parolini, Barbara; Palmieri, Michele; Finzi, Alessandro; Frisina, Rino
Purpose: To propose the Myopic Traction Maculopathy (MTM) management Table, based on the MTM Staging System (MSS). Methods: A retrospective review of 157 eyes affected by MTM, operated with pars plana vitrectomy (PPV), or macular buckle (MB) or combined surgery (MB + PPV). Each case was classified according to the MSS. Anatomical results were evaluated with OCT at an intermediate follow-up (3–6 months) and at a final follow-up (2–8 years), considering changes both in the foveal and in the retinal pattern. The number and type of operations needed were noted. The surgical complications were reported. Results: Primary surgery was MB for 83 eyes (52%), PPV for 36 (23%) and MB + PPV for 38 (24%). At intermediate follow-up, the retinal pattern was restored in 55.41% and foveal in 42.68%. Further surgery was indicated as PPV in 25.48%, MB in 14.65%. At the final follow-up, the retinal pattern was restored in 96.16% and the foveal pattern in 87.90%. BCVA improved at the final follow-up ( p < 0.05). The complications of MB were not sight-threatening. The complications of PPV were FTMH in 67% cases in stages 2, 3, and 4. Cataract developed in 60% of phakic eyes. The complications of combined MB+PPV were cataract (56%) and PVR (5%). Conclusions: Both PPV and MB may be used to treat MTM. PPV addresses the changes in the foveal pattern while MB addresses the changes in the retinal pattern. The MTM management table offers a proposal for the choice of type and timing of treatment customized per each stage of MTM.